تقصي متبقيات المبيدات الكلورية العضوية في الرسوبيات وبعض الرخويات في ساحل طرطوس - غانم, اياد; عمار, ازدهار; العرفي, مالك (Latakia University Journal -Biological Sciences Series, 2016)
دُرس تركيز ثمانية مبيدات كلورية هي: gamma HCH، Heptachlor، Heptachlor epoxide، Aldrin، Dieldrin، 4,4,DDE، 4,4,DDD، 4,4,DDT في أنواع من الرخويات هي: Monodonta turbinata, Brachidontes variabilis , Patella caerulea, Trochus erithraeus, Strombus persicus والرسوبيات في خمسة مواقع هي: مصب نهر السن، مصب نهر جوبر، محطة بانياس الحرارية، موقع الباصية ومصب نهر مرقية ضمن ستة أزمنة لجمع للعينات خلال عامي 2006 – 2007.أشارت نتائج الدراسة إلى أن أعلى مراكمة للمبيدات الكلورية كان في مصب نهر السن، مصب نهر جوبر، ومصب مرقية حيث راكمت الرخويات المدروسة تراكيز مختلفة من جميع المبيدات الكلورية الثمانية المدروسة، أما موقع المحطة الحرارية، فقد كان مبيدا الـ Heptachlor والـ Heptachlor epoxide هما المركبان الرئيسان، في حين كانت تراكيز الملوثات (المبيدات) في موقع الباصية أقل من بقية المواقع. Concentrations of eight chlorinated pesticides: namely, gamma HCH, Heptachlor, heptachlore epoxide, aldrin, dieldrin, 4,4-DDE, 4,4-DDD, and 4,4-DDT were studied in some mollusks species Monodonta turbinata, Brachidontes variabilis , Patella caerulea, Trochus erithraeus, Strombus persicus and in sediments taken from five different locations: Assin estuary, Jobar estuary, Banias Thermal Electricity Station, Albasia, and Mirkiya River estuary. Sampling was performed at six different times during the period 2006-2007.Results indicated that Assin estuary contained the highest level of contamination followed by Jobar estuary and Mirkiya estuary where sampled mollusks species contained various concentrations of all of the studied pesticides. At Banias Thermal Electricity Station samples showed contamination with heptachlore and heptachlore epoxide only, whereas the concentration of pesticides at Albasia location, much lower than the other locations.